2013
DOI: 10.1021/ef401928c
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Alteration of the Quartz Surface in the Presence of Metal Cations

Abstract: Experimental research was conducted to clarify the wettability alteration mechanism in the presence of metal cations. Wettability was studied by measuring the contact angle on a quartz–crude oil–water system. The quartz surface is aged in an asphaltene/toluene solution to study the effect of aging time, asphaltene concentration, water film on the quartz surface, and metal cations in the water film on wettability alteration of the quartz surface. The quartz surface property is characterized with ζ-potential mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 29 publications
3
40
0
1
Order By: Relevance
“…The adsorption is pH-dependent, indicating that there is cation exchange with H + as well. Other studies have confirmed that the presence of Ca 2+ and Mg 2+ are important for the adsorption of asphaltenes on quartz [27,28]. Thus it is plausible that the two chemical mechanisms can also occur on quartz surfaces, not just on clays, and may be responsible for part of the LSE observed in the clay-free rocks.…”
Section: Double-layer Expansion (Dle) and Two Chemical Mechanismsmentioning
confidence: 90%
See 1 more Smart Citation
“…The adsorption is pH-dependent, indicating that there is cation exchange with H + as well. Other studies have confirmed that the presence of Ca 2+ and Mg 2+ are important for the adsorption of asphaltenes on quartz [27,28]. Thus it is plausible that the two chemical mechanisms can also occur on quartz surfaces, not just on clays, and may be responsible for part of the LSE observed in the clay-free rocks.…”
Section: Double-layer Expansion (Dle) and Two Chemical Mechanismsmentioning
confidence: 90%
“…At 1 mM, the zeta potential for all three brine/silica dispersions is − 33 mV so that the change with salinity is more pronounced for the larger cations. At the same concentration, the brine/rock and brine/oil zeta potentials tend to be more negative if the brine contains monovalent cations as opposed to divalent cations [29,32,27]. This may be because divalents have a stronger influence on the ionic strength and electrostatic screening as evident in Eq.…”
Section: Zeta Potential Contact Angle Oil Recovery and Afm Measurementioning
confidence: 99%
“…The contact angles of FPDD surfactant solution on a lipophilic quartz-slide surface were measured using the Fig. 3 The IFT between the FPDD surfactant and crude oil at 90 C pendant drop method (Qi, Wang, He, Li, & Xu, 2013). The wettability alteration performance was evaluated by the contact angle variation before and after adsorption of the FPDD surfactant on the surface of the lipophilic quartz slide.…”
Section: Wettability Alterationmentioning
confidence: 99%
“…The contact angles were determined by the sessile drop method using a JC2000D contact angle measurement apparatus (Shanghai Zhongchen Digital Technology Co., Ltd., China) at room temperature [20]. Quartz plates were used to simulate the sandstone surface during the contact angle measurement.…”
Section: Contact Angle Measurementmentioning
confidence: 99%